The effect of PLA-based composite material history on its electret properties - Zagidullina Inna; Guzhova Alina; Karulina Elena; Kulemina Sofya (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
This study reveals the effects of manufacturing methods and composition of the films based on polylactic acid (PLA) and fine fillers of different nature (aerosil, white silica and starch) and concentration on the electret properties (EP). The methods were solution casting (I) and compression molding (II). PLA films manufactured via method II exhibited a significantly higher electret effect when subjected to unipolar corona discharge than the films obtained by method I. The difference in the EP was proved to be attributed to the presence of polar liquid molecules (trichloromethane, water) within the samples produced using method I enhancing the electrical conductivity of the samples. The samples showed a tendency for the EP parameters to increase when the dispersed particles of fine fillers were added to the pure PLA. An explanation for this phenomenon has been proposed. The composition of PLA with 4% white silica had the best electret properties.